Calibrating Contentment: The Metrics of Health and Happiness - Ramirez de Arellano, Annette B. (Puerto Rico Health Sciences Journal, 2014)
This historical note examines Puerto Rico’s pioneering role in the development of happiness studies. In 1963-64, the Puerto Health Department’s Master Sample Survey included a series of questions on well-being to tap into self-assessed happiness. The study found that happiness was positively correlated with income, education, and health. It also found that women were less happy than men, and that well-being was negatively correlated with age. Since then, the metrics of happiness have gained currency, and several countries have adopted indices to measure their population’s self-perceived well-being. Studies have also documented the reciprocal relationship between health and happiness.